Using Metaphors to Facilitate Exploration of Emotional Content in Counseling With College Men. Issue 2 (June 2017) - Genuchi, Matthew C.; Hopper, Brian; Morrison, Charles R.
Mental health professionals in college counseling centers are increasingly interested in understanding the challenges of effectively working with male college students. Not all men are difficult to work with in therapy, but certain masculine gender role norms, particularly restricted emotionality, can create challenges to the therapeutic process. However, therapeutic metaphors that are familiar to male clients can provide a safe entry point to emotional topics. We describe a framework of using metaphors with college men that involves connecting with interests of male clients, establishing rapport, and facilitating a nonthreatening common language to develop metaphors for exploration of vulnerable emotions. Brief case examples are then used to illustrate effective implementation of therapeutic metaphors with traditional male clients experiencing difficulty with emotions.